Assessing Spiritual Distress in Post-Operative Orthopedic Patients: A Descriptive Study at dr. Soebandi Regional Hospital, Jember - Mulia Hakam; Lula Apriliya Puteri Bintari; Jon Hafan Sutawardana (Al-Hijrah Indonesia, 2025)
Background: Spiritual distress is a problem with the patient's response to health. Spiritual distress is a disturbance in the meaning of life about oneself, others, and God. Spiritual distress occurs due to spiritual needs not being met. Purpose: This study aims to determine spiritual distress in post-operative orthopedic patients in the surgical room at dr. Soebandi Regional Hospital Jember. Methods: This study employed a descriptive, consecutive sampling method involving 150 respondents from both major and minor post-operative orthopedic patients in 2023. Results: The majority of respondents in this study were men with varying ages and types of surgery, 80.7% experienced major surgery, and 19.3% underwent minor surgery. Data collection was conducted using the Spiritual Distress Scale questionnaire, and the results showed a median value of 74.00, with a minimum value of 33 and a maximum value of 103. This indicates that the resulting value is close to the maximum value of the questionnaire, suggesting a high level of spiritual distress. This can be caused by the high value placed on self-relationship, which encompasses the strengths that exist within a person, including knowledge and attitudes about oneself. This high value can occur due to a lack of knowledge about oneself and a lack of confidence in the future, leading to a loss of peace of mind. Conclusion: This research provides additional data and knowledge regarding spiritual distress in post-operative orthopedic patients. Patients with spiritual distress require maintenance of spiritual well-being, which helps them find meaning in life and experience a sense of peace. The results of this research make it possible for nurses to develop and understand the importance of spiritual care for patients